Modelling impacts of utility-scale photovoltaic systems variability using the wavelet variability model for smart grid operations. (February 2019) - Emmanuel, Michael; Rayudu, Ramesh; Welch, Ian
Abstract: The increasing presence of large-scale photovoltaic (PV) systems in the distribution network requires a thorough interconnection study for effective planning and reliable grid operations. The proliferation of such systems now creates a critical need for their accurate modelling to enable planners and operators understand and fully characterize centralized PV variability with the ability to develop realistic projections of PV plant output variability. This article models impacts of variability and the locational value of such utility-scale (centralized) PV plants deployed close to distribution feeder source, midpoint and end using the wavelet variability model (WVM). This model is used to accurately simulate solar irradiance variability and the PV plant output taken into account its entire footprint and density, time series irradiance data from a single point sensor, and location-dependent cloud-speed coefficient. Also, since the variability observed from a single point irradiance sensor cannot provide the exact variability across the entire PV plant, this study uses a high-frequency solar irradiance data and geographic smoothing for accurate modelling of PV output variability. Further, impacts on the tap changer operation, voltage profile, load demand offset and line loading reduction on the IEEE-34 distribution test feeder are investigated.